An Investigation Study of Thinning Distribution in Single Point Incremental Forming Using FEM Analysis - Doss, Qasim Mohamed; Abaas, Tahseen Fadhel; Bedan, Aqeel Sabree (Al-Khwarizmi Engineering Journal, 2013)
Single Point Incremental Forming (SPIF) is a forming technique of sheet material based on layered manufacturing principles. The sheet part is locally deformed through horizontal slices. The moving locus of forming tool (called as toolpath) in these slices constructed to the finished part was performed by the CNC technology. The toolpath was created directly from CAD model of final product. The forming tool is a Ball-end forming tool, which was moved along the toolpath while the edges of sheet material were clamped rigidly on fixture.This paper presented an investigation study of thinning distribution of a conical shapes carried out by incremental forming and the validation of finite element method to evaluate the limits of the process as regards to the geometry of the final product.Three conical products have been carried out during this study with different forming angles and depth. The process was simulated using FEM program (ANSYS 11.0) and the results showed that the deviations between simulated and real values did not exceed of 6%.